Abundance, density and habitat use of lowland paca (Cuniculus paca, Rodentia: Cuniculidae) in the Lacandon Rainforest, Chiapas, Mexico - Figueroa-de-Leon, Avril; Naranjo, Eduardo J.; Perales, Hugo; Santos-Moreno, Antonio; Lorenzo, Consuelo (THERYA, 2017)
In this study, the effect of relevant variables (availability of food and cavities, competition, predation, and hunting pressure) on the relative abundance and population density of the spotted lowland paca (Cuniculus paca) was assessed. In addition, habitat use of this species at three sites with different land use regime (Montes Azules Biosphere Reserve, community reserves, and anthropic sites) in the Lacandon Rainforest, Chiapas, Mexico was analysed. From the perspective of the source-sink systems, it was predicted that pacas selectively would use the habitat with higher food and cavity availability (source habitats), where higher densities were expected. Twelve transects were located in three sites with different land use regimes, where food availability and potential cavities used by pacas were assessed. Along these transects, 4 camera-traps were deployed every 200 meters to estimate the relative abundance of pacas and their potential competitors and predators. Photo-captured individuals were identified to estimate population density and seasonal variation in habitat use. Generalized linear models (GLM) were constructed to analyse the effects of several variables on paca abundance and density. A relative abundance of 0.05 and 0.08 paca photographs/100 camera-days were recorded in the dry and the rainy season, respectively. A density of 54 pacas/km2 was estimated in both seasons. The availability of cavities was the only variable that showed a significant effect on paca density (P = 0.04 for the dry season, and P = 0.006 for the rainy season). Community reserves were used in the dry season more than expected from their availability in the study area (x2 = 28.8; P = 0.0001). In the rainy season, all three sites were used by paca in proportion to their availability. Our results suggest that the cavities used as refuges by pacas drive their population dynamics, and constitute a key habitat resource for them in the study area. We propose that the Ejidal Reserve and Montes Azules Biosphere Reserve may be source habitats supporting higher paca densities and greater availability of adequate cavities to protect adults and their offspring. On the other hand, areas transformed into croplands and grasslands for livestock production would represent sink habitats with lower paca densities, less availability of adequate cavities, and absence of offspring. The long-term conservation and habitat management of pacas in transformed landscapes will probably rely on the distribution and connectivity between and within the different habitat types available in the study area.